Halal Certification and Value Addition for MSME Products: A Literature Review on Government Initiatives and Regulatory Frameworks - Sunarta, Desy Arum; Apriliani, Riski; Prasetya, Agung; Ramadhaningsih, Dwi (Malacca: Journal of Management and Business Development, 2025)
This study aims to explore the role of halal certification in enhancing the value of Micro, Small, and Medium Enterprises (MSMEs) products through a review of existing literature and policy frameworks in Indonesia. The research adopts a qualitative systematic literature review method by analyzing national regulations, policy initiatives, and previous empirical studies relevant to halal certification and MSME development. A total of 41 publications from 2020 to 2024 were reviewed, encompassing government reports, scholarly articles, and institutional documents related to the implementation of halal assurance systems. The findings indicate that halal certification contributes significantly to increasing product value, market competitiveness, and consumer trust. The Indonesian government, through the Halal Product Assurance Organizing Agency (BPJPH) and the SEHATI program, has played an important role in facilitating certification processes and strengthening institutional collaboration. However, several challenges remain, including limited financial capacity, technical constraints, low awareness among MSME owners, and the complexity of administrative procedures. The study concludes that effective halal certification requires synergy between regulatory enforcement, financial and technical assistance, and continuous education to enhance MSME readiness. Strengthening digital infrastructure, simplifying verification mechanisms, and promoting stakeholder collaboration are essential for accelerating halal certification and ensuring sustainable MSME growth in Indonesia.